2022
DOI: 10.3390/cancers14102389
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Positive Lymph Nodes and Resection Margin Status on the Overall Survival of Patients with Resected Perihilar Cholangiocarcinoma: The ENSCCA Registry

Abstract: Background: Lymph node metastasis and positive resection margins have been reported to be major determinants of overall survival (OS) and poor recurrence-free survival (RFS) for patients who underwent resection for perihilar cholangiocarcinoma (pCCA). However, the prognostic value of positive lymph nodes independently from resection margin status on OS has not been evaluated. Methods: From the European Cholangiocarcinoma (ENSCCA) registry, patients who underwent resection for pCCA between 1994 and 2021 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…29% of the whole cohort of BTC patients were eligible for curative surgery, of which 60% relapsed within 2 years. We confirmed that the most accurate prognostic factor for relapse was the lymph-nodal status, as previously reported [ 21 ]. Interestingly, we did observe a high correlation between positive nodal status and microscopic vascular invasion (93%), suggesting that in those cases where assessment of lymphoadenectomy is considered (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…29% of the whole cohort of BTC patients were eligible for curative surgery, of which 60% relapsed within 2 years. We confirmed that the most accurate prognostic factor for relapse was the lymph-nodal status, as previously reported [ 21 ]. Interestingly, we did observe a high correlation between positive nodal status and microscopic vascular invasion (93%), suggesting that in those cases where assessment of lymphoadenectomy is considered (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…There is a well-established emphasis on pathology in predicting likely outcomes by considering the recognised negative prognostic indicators of tumour size, positive resection margins and nodal involvement. 37 Lymph node involvement is independently associated with a high risk of early relapse and adequate lymphadenectomy should be standard in patients undergoing liver resection due to the survival benefit, even in clinically node negative iCCA. 38 Recently, Lamarca et al 39 proposed a modification to staging classifications to account for the significantly worse prognosis observed in iCCA if liver metastases present, irrespective of lymph node status.…”
Section: Patient Stratification and Biomarkers For Adjuvant Chemotherapymentioning
confidence: 99%
“…In line with these findings, an older study from Japan showed that hemi-hepatectomy associated with wide lymph node dissection, extended beyond the regional lymph nodes to the para-aortic site, had curative effects on the 5-year survival in iCCA [ 6 ]. Finally, a recent work based on the European Network for the Study of Cholangiocarcinoma (ENS-CCA) registry confirmed that in the case of positive lymph nodes, the state of the resection margin does not influence OS or recurrence-free survival (RFS) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%